Nowa treść kary ograniczenia wolności - Pietruszka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The penalty of restriction of liberty functions in the Polish criminal law as of 1st January, 1970. The Penal Code of 1969, which introduced this penalty, stated it to be an adjudicated punishment ranging from 3 months to 2 years, in three variants: unpaid, nonsupervised work towards community purposes, deductions of some part of remuneration and referral to work with obligatory deduction. Regardless of the form of punishment, the convicted must adhere to certain additional duties, which subsisted on them under the law or were imposed by the Court. The Act also provided for the possibility of modification of the sentence in the specified range in the proceedings.The legislative body reduced the penalty of restriction of liberty in the Penal Code of 1997 from 1 month to 12 months and abolished the form which was to refer the offender to work and withhold some part of the remuneration. Maintaining the extra obligations arising from the Act, however only slightly trimmed, it created a wider possibility of educational influence on the offender through the development of a directory of facultative responsibilities and an authorization by the court of probation officer supervision or another entity. Due to retaining the possibility of making changes during the execution of the penalty of restriction of liberty, it widened their scope. The original content of the penalty of restriction of liberty was subject to different changes, for example in 2010 supervision was abolished, while allowing for the use of a larger range of facultative duties.However, the most serious changes that “hit” the penalty of restriction of liberty were implemented by the Act of 20 February, 2015 with effect from 1 July, 2015, which raised the maximum statutory punishment up to 2 years, but above all performed its significant development. In place of the two main characteristics it introduced much more variants of this punishment. The penalty of restriction of liberty may, in fact, currently rely on: 1 the obligation to perform unpaid, non-supervised work towards community goals, 2 the obligation to remain in the place of residence or other designated area, with the use of electronic surveillance system, 3 the obligation as stated in article 72 § 1 items 4–7a of the Penal Code, 4 deduction of some part of the remuneration. The above obligations and deduction can be adjudicated separately or in overlapping with another or others, in any combination. Thus it can be calculated, assuming the form of punishment referred to in point 3 as unitary entailing actually a few options, that the penalty of restriction of liberty may occur in 15 major variants. In the literature it is also allowed to form a sequential content of penalty obligations which are to be carried out in a fixed order, including when they partially overlap. In any case, the sentenced to the restriction of liberty is further required to submit explanations concerning the course of detention and cannot change their habitual residence without the consent of the court. Yet there is the possibility to adjudicate certain obligations which are optional. Quite a wide range of possibilities for modifying the contents of the penalty of restriction of liberty in its executive phase must also be mentioned.All the above means that, at present, the penalty of restriction of liberty presents itself as a measure which carries a great deal of potential, creates wide opportunities for the customization of criminal-law response to crime, but also as a measure which may give rise to serious problems both at the stage of adjudicating the punishment, but probably even more at the stage of its implementation, and certainly will require a great commitment on the part of the authorities who apply and carry out this punishment also in terms of making the offender aware of its content.
Keywords: prawo karne; kara ograniczenia wolności; prace społeczne; potrącenie części wynagrodzenia za pracę